How They Lived in Cities Long Ago - Unstead, R. J. (Arco Publishing, Inc. New York, 1980)
Depicts the daily life in the cities of ancient civilizations in countries such as China, Egypt, Greece, and Mexico
Includes index
9 - 12 years
Keywords: City Histroy -- Juvenile Literature